Juegos didácticos interactivos como estrategia de aprendizaje para la enseñanza de lectoescritura de 6° año paralelo “D” de EGB de la UE “Miguel Ángel Pontón” de la ciudad de Riobamba periodo2020 - 2021. - Gallegos Donoso, Moisés Alonso (2021)
The objective of this research was to analyze the literacy learning context related to the use of interactive didactic games in 6th Parallel Year "D" of Basic General Education of the "Miguel Ángel León Pontón" Educational Unit of the city of Riobamba period 2020 -2021, the focus of this research is mixed since it integrates both "qualitative" and "quantitative" approaches, arguing that testing a theory through two methods can obtain more reliable results that support our research. The study population was sixth grade teachers, a structured survey was used as a data collection instrument, which was applied through google forms, and an observation sheet that allows the analysis of a specific situation, through indicators that allow collecting more real and concrete data. This research provides relevant findings in the teaching practice of the study population, such as the use of active learning directly related to the development of reading and writing skills, with an emphasis on active learning, using games as didactic resources. Varied at different times of learning. We conclude that it is important to stimulate the reading and writing process from the elementary basic education levels using strategies related to the social and cultural context of the child.